Description of blaKPC-carrying Escherichia coli in patients from a Brazilian hospital over a 4-year period - Pradela, Letícia Kalir; Casella, Tiago; Manieri, Fernanda Zani [UNESP]; de Andrade, Letícia Kellen; Barroso, Marlon do Valle; Nhu, Nguyen Thi Khanh; Schembri, Mark Andrew; Moreira, Cristiano Gallina [UNESP]; Nogueira, Mara Corrêa Lelles (Elsevier, 2025)
Klebsiella pneumoniae carbapenemase (KPC)-producing Escherichia coli are recognized by the World Health Organization as a critical group of bacterial priority pathogens of public health importance. Thus, increased understanding of the genetic characteristics of KPC-producing E. coli is required. Here, we performed a retrospective study in a Brazilian teaching-hospital to describe the genomic features linked to antimicrobial resistance, virulence, and phylogeny of 40 meropenem-resistant E. coli. All isolates carried the blaKPC-2 gene, but amikacin, tigecycline, colistin, polymyxin B, and fosfomycin showed good activity. Molecular typing by MLST revealed 20 sequence types (STs), with a predominance of ST131. Whole-genome sequencing identified Tn4401 as a mechanism responsible for blaKPC-2 mobilization, a variety of antimicrobial resistance and virulence genes, the predominance of pathogenic phylogroup lineages, and the grouping of genomes belonging to the same ST. KPC-producing E. coli is not a common pathogen, but few treatment alternatives are available against potentially virulent strains.
Keywords: Carbapenemase; Epidemiology; Multidrug-resistance; Uropathogenic Escherichia coli; Whole-genome sequencing